Caught in a vicious cycle? Explaining bidirectional spillover between parent-child relationships and peer victimization - Kaufman, Tessa M.L.; Kretschmer, Tina; Huitsing, Gijs; Veenstra, René (Development and Psychopathology, 2019)
Relationships with parents and peers are crucial for children's socialization, but how parent-child and peer relationships mutually affect each other is not well understood. Guided by spillover theory, we zoomed in on the bidirectional interplay between parental rejection and warmth on the one hand and peer victimization on the other, and examined whether children's maladjustment symptoms mediated hypothesized cross-domain spillover effects. Data stem from five waves of the longitudinal KiVa study among 9,770 children (50% boys; mean age = 9.16, standard deviation = 1.29). Results from random intercept cross-lagged panel models showed that higher parental rejection and lower parental warmth predicted increases in peer victimization and vice versa across waves, thus supporting the bidirectional model. Moreover, spillover from parent-child rejection and warmth to peer victimization was partially driven by children's depressive symptoms and bullying perpetration. Vice versa, spillover from peer victimization to parent-child rejection and warmth was partially driven by children's social anxiety, depressive symptoms, conduct problems, and bullying perpetration. Thus, children might get caught in persistent problems in two important social domains, and these two domains influence each other through children's maladjustment. Family and school interventions should be integrated to prevent a downwards spiral.
CRIS-Team Scopus Importer:2025-03-19
Keywords: maladjustment symptoms; parent-child relationships; peer victimization; spillover